Penghayatan Agama (Religiositi) dalam pembangunan keusahawanan - Abdul Hamid, Solahuddin; Ishak, Mohd Sobhi; Hashim, Hydzulkifli (UUM Press, 2017)
Religion is no longer considered as the main obstacle, but it has become a motivating factor for the development of entrepreneurship management. However, a lot of research on entrepreneurship and its relation to religious values in terms of terminology, theoretical models, concepts and empirical been pioneered by the non-Muslim scholars either from the West part or the East part. In this case, the difference result is considered to be a reasonable based on the difference angle such as religion, culture and the background knowledge. This spiritual element has been discussed in a huge concept according to each religion itself. This study only focused on the Islamic religious dimension that related with faith, Sharia and morals associated with personality and behavior of respondents in the business sector only. The data obtained through questionnaires distributed among small entrepreneurs under Majlis Amanah Rakyat (MARA) in Kedah. The study found that the level of management religious practice among entrepreneurs is high and their impact on entrepreneurial activity in line with their identity as Malays. Hopefully, the results of this study can help MARA and other government agencies to develop the management of entrepreneurial competence plans to be more holistic